Hydraulic Abrasion-Resistant Elastic Epoxy Resin Materials - Liqun Xu; Kai Zhang; Yanhui Liu (Advances in Materials Science and Engineering)
The abrasion of hydraulic concrete structures caused by the washing action of flowing water is a common problem and cannot be solved by simply increasing the strength of the concrete. To ensure safe operation, increase in service life and reduction of maintenance costs of hydraulic concrete structures and the development of abrasion-resistant materials are required. In this work, polyurethane-modified epoxy resin was synthesized using the interpenetrating network technology (IPN). After many mixing experiments, the ratio of polyether amine to alicyclic amine in Component B was determined to be 29 : 14 and the ratio of Component A to Component B was 7 : 3. With these ratios, elastic epoxy achieved a tensile strength of more than 15 MPa and an elongation rate of more than 20%, thus balancing strength and toughness. The effects of the curing conditions, the ratio of Component A to Component B, and diluents and fillers on tensile strength and elongation of the elastic epoxy resin were analyzed. The results of the analysis indicated that the curing duration should be over 7 days, the optimal proportion of Component A to Component B should be 7 : 3, and the diluent of the elastic epoxy material should be the bifunctional butanedioldiglycidyl ether (622). The reliability of this material was determined by pull-out testing, adhesion, and tensile strength testing. The underwater steel ball test and ring test were adopted as the abrasion-resistance tests for the elastic epoxy resin material. The results showed that the abrasion-resistance performance of elastic epoxy coating improved hundreds of times over that of common concrete. Although the wearing strength was reduced with pressure, the elastic epoxy coating still retained excellent abrasion-resistance performance. At last, future application prospects of elastic epoxy improvement products are introduced and need further reach.